2018
DOI: 10.1002/minf.201800080
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potent Panobinostat Histone Deacetylase Inhibitor Derivatives: Molecular Considerations for Enhanced Isozyme Selectivity between HDAC2 and HDAC8

Abstract: Histone Deacetylases (HDACs) are an important family of 18 isozymes, which are being pursued as drug targets for many types of disorders. HDAC2 and HDAC8 are two of the isozymes, which have been identified as drug targets for the design of anti-cancer, neurodegenerative, immunological, and anti-parasitic agents. Design of potent HDAC2 and HDAC8 inhibitors will be useful for the therapeutic advances in many disorders. This work was undertaken to develop potent HDAC2 and HDAC8 inhibitors. A docking study was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…A mode of binding having bidentate coordination of the Zn 2+ atom with the hydroxamate tail was produced, which is consistent with crystal structures of other hydroxamic acid HDAC inhibitors [2,21,23,24]. Similar to panobinostat, the cyclopropane derivatives were shown to be able to participate in π-π stacking interactions within the core of the active site between the residues Phe-812 and Phe-871 lining the gorge [25]. The benzene ring was shown to be positioned within the LSP of HDAC4.…”
Section: Docking Analysis Of Original Cyclopropane Hydroxamic Acid Desupporting
confidence: 71%
See 2 more Smart Citations
“…A mode of binding having bidentate coordination of the Zn 2+ atom with the hydroxamate tail was produced, which is consistent with crystal structures of other hydroxamic acid HDAC inhibitors [2,21,23,24]. Similar to panobinostat, the cyclopropane derivatives were shown to be able to participate in π-π stacking interactions within the core of the active site between the residues Phe-812 and Phe-871 lining the gorge [25]. The benzene ring was shown to be positioned within the LSP of HDAC4.…”
Section: Docking Analysis Of Original Cyclopropane Hydroxamic Acid Desupporting
confidence: 71%
“…The benzene core of panobinostat can participate in π-π stacking interactions with the Phe-Phe motif, while vorinostat having a purely aliphatic linker region cannot. Currently, the inclusion of heteroaromatic rings used in hydroxamic acid derivatives for HDAC inhibitors development has also been evaluated [16,21,22,25]. In studies focused on HDAC4, tandem aromatic rings cores have also been explored, evaluating ring systems combining either two 6-membered aromatic rings, or an aromatic 6-membered and aromatic 5-membered bound to each other [16,21,22].…”
Section: Heteroatoms In the Innermost Aromatic Ring Of The Scaffoldmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in Class I HDAC inhibition, there remains an obvious need to develop compounds having better therapeutic properties as a single-agent therapeutic drug. Our recent research based on computational studies indicated heterocyclic cores as suitable surrogates for the central core of the hydroxamate derivative, panobinostat [12]. It should be noted that TOI3-rev in this article is different from TOI3 in the previous reporting [12].…”
Section: Introductionmentioning
confidence: 70%
“…Our recent research based on computational studies indicated heterocyclic cores as suitable surrogates for the central core of the hydroxamate derivative, panobinostat [12]. It should be noted that TOI3-rev in this article is different from TOI3 in the previous reporting [12]. Here, the 1,2-diazole ring has been replaced with that of a pyrimidine core.…”
Section: Introductionmentioning
confidence: 85%